When sleeping dogs wake up : Norway and justice and home affairs in the European Union - Muth, Frauke (Zentrum für Europäische Integrationsforschung (ZEI), 2007)
The following essay is based on the assumption that the Norwegian government is interested in making the best possible use of its association with Schengen, and to find more forms of cooperation beyond the status quo, but without becoming member of the European Union in the short- to medium term.6 Having this in mind, the paper tries to answer the following questions: Does Norway make exhaustive use of its possibilities to shape decisions within Schengen, taking into account formal and informal channels of influence? Moreover, to what extent is a further linkage to the EU’s JHA policies beyond present agreements possible? The first statement of this paper is that Norway does not fully use its opportunities provided through the Schengen agreement. It is argued that it does make considerable use of formal possibilities within the Schengen agreement, and that this is mainly due to the pressure of participation in the working structures of the Council of the EU.7 But Norwegian EU policy tends to be less committed with regard to informal channels of influence outside the Council structures. The second statement of the paper is that a further linkage of Norway to JHA policies beyond Schengen is restricted by three main problems: (1) the occurrence of legal or constitutional barriers stemming from Norway’s third country status that hamper ad-hoc agreements equivalent to original EU policies, (2) the potential lack of congruence with political aims of other EU-outsiders such as Iceland or Switzerland, and (3) the political motivated reluctance of member states to grant Norway a broader role in the field of JHA.